Model Pemberdayaan Desa Berkelanjutan Dalam Perspektif Feminis - Zakiah, Siti; Mardiyana, Eva; Apriadi, Akhmad Niko (Universitas Negeri Padang, 2024)
In patriarchal cultures, women often face constraints in participation and empowerment in the tourism sector. This research objective to examine the model of sustainable village empowerment in the perspective of feminism in Bandung Regency. A qualitative approach with a case study method in Bandung Regency was employed. Data collection involved in-depth interviews with relevant stakeholders, participatory observation, and analysis of documents related to village empowerment in tourism. Interpretative analysis was conducted with interactive procedures. The research findings indicate that the model of sustainable village empowerment from a feminist perspective involves several key elements. This entails support for the development of micro and small businesses owned by women, skills training, and access to fair capital and markets. Feminist perspectives significantly contribute to feminist thought, expanding the understanding of women's empowerment as a struggle for individual freedom and equality amidst the complexity of social, political, and cultural relationships in the empowerment of sustainable village tourism